Bibliometric Insights into Shared Leadership: Integrating Islamic Leadership and Entrepreneurship Values - Hendratmi, Achsania; Ratnasari, Ririn Tri (Journal of Leadership in Organizations, 2025)
Introduction/Main Objectives: This study explores shared leadership approaches integrating Islamic leadership and Islamic entrepreneurship values using bibliometric methods. The research aims to provide insights into shared leadership development and its connection to Islamic principles. Background Problems: Shared leadership is an emerging paradigm in leadership studies, focusing on team performance, virtual collaboration, and cultural diversity. However, its linkage with Islamic values such as justice, deliberation, and blessings remains underexplored. This gap highlights the need for further investigation. Novelty: The novelty of this research lies in mapping shared leadership literature from 1996 to 2024 and uncovering its potential integration with Islamic values. This perspective has not been addressed comprehensively in prior studies. Research Methods: This study conducts a bibliometric analysis of 437 documents from the Scopus database. The study identifies trends, dominant themes, and contributions from authors and institutions in shared leadership research. Findings/Results: The findings reveal the significant growth of shared leadership research, emphasizing team performance, virtual collaboration, and cultural diversity. This study highlights the potential of Islamic leadership principles to enhance team collaboration, justice, shura (deliberation), blessings, and ta'awun (cooperation). Conclusion: This research provides new insights into integrating spiritual and professional values in modern leadership theory. Shared leadership in the context of Islamic entrepreneurship emerges as an inclusive, socially impactful model. The study offers strategic directions for future research and practical applications.